NVivo+ Workshop: Capacity development for qualitative data coding and analysis using NVivo - DuttaGupta, Tanaya (International Livestock Research Institute, 2024)
A full-day workshop for capacity development on qualitative data analysis using NVivo was organized and conducted by Tanaya DuttaGupta, a postdoctoral fellow working on social differentiation and climate change in the Livestock, Climate, and Environment program at ILRI, Nairobi, on July 5, 2024. The workshop focused on technical capacity building in NVivo, and on understanding and applying approaches for qualitative data coding and analysis through a social inclusion lens.